Blurring of inappropriate scenes in a video using image processing - Islam, Rahat Shahriar; Siddiqui, Raisa; Roy, Dipta (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.